Die kgl. Glasmalereianstalt in München 1827 - 1874 : Geschichte, Werke, Künstler - Vaassen, Elgin (Kunstwissenschaftliche Studien, 2013)
"The kgl. Glasmalereianstalt Munich produced pictorial stained glass windows that were modeled on the works of leading Nazarene artists, and their innovative painting technique heralded an entirely new style of glass painting. This book documents the works produced at the Glasmalereianstalt and presents new source material on and illustrations of the techniques developed by these Munich artists."--Publisher's English website